Trial leadership by women is associated with racial diversity among heart failure clinical trial participants: a systematic bibliometric review 2000–2020. (14th October 2021) - Wei, S; Le, N; Zhu, J W; Breathett, K; Greene, S J; Mamas, M A; Zannad, F; Van Spall, H G C
Abstract: Background: For the results of randomized controlled trials (RCTs) to be generalizable, they should report on and include the broad range of patients who have the disease. Purpose: We assessed temporal trends and trial factors associated with 1) the reporting of race or ethnicity data and 2) the enrolment of Black, Indigenous, and people of colour (BIPOC) in Heart Failure (HF) RCTs. Methods: We searched MEDLINE, EMBASE, and CINAHL for RCTs that recruited adults with HF and were published in journals with an impact factor ≥10 between January 1, 2000 and June 17, 2020. We extracted data in duplicate and used the Cochran-Armitage and Jonchkeere-Terpstra tests to examine temporal trends. We used multivariable regression to assess the independent association between trial factors and the outcomes of interest. Results: A total of 414 RCTs met inclusion criteria, of which a vast majority (90.6%; 95% CI 87.4–93.2%) were coordinated in either Europe or North America. Only 157 of the 414 RCTs (37.9%; 95% CI 33.2–42.8%) reported race/ethnicity data; among the 158, 200 participants in these trials, only 29, 512 (18.7%; 95% CI 18.5–18.9%) were BIPOC. There was a significant increase in the reporting of race or ethnicity data (from 26.9% in 2000–2001 to 54.2% in 2019–2020, p<0.001) and in enrollment of BIPOC (from 16.5% in 2000–2001 to 23.9% in 2019–2020, p=0.038) between 2000–2020. Trial leadership by a woman was associated with twice the adjusted odds of reporting of race or ethnicity data (OR 2.0; 95% CI 1.1–3.8; p=0.028) and an 8.4% (95% CI 1.9–15.0%; p=0.012) adjusted increase in enrollment of BIPOC. The race/ethnicity of trial leaders was not available for analysis. Conclusions: Among HF RCTs published between 2000–2020, <38% reported data on race or ethnicity, although this increased over time. Among trials reporting such data, <19% of participants were BIPOC, with modest increases in enrollment over time. Trials led by women had greater adjusted odds of reporting race/ethnicity data and enrollment of BIPOC. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): CIHR